Pelleting characteristics of selected biomass with and without steam explosion pretreatment - Adapa, Phani; Tabil, Lope; Schoenau, Greg; Opoku, Anthony (International Journal of Agricultural and Biological Engineering, 2010)
Processing and densification of agricultural biomass into high density and durable pellets are critical to facilitate handling, storage and transportation. Biomass pelleting experiments were designed to conduct single and pilot scale pelleting of non-treated and steam exploded barley, canola, oat and wheat straw grinds acquired from 6.4, 3.2, 1.6 and 0.8 mm hammer mill screen sizes at 10% moisture content (wb). Single-pelleting was performed by applying compression pressures of 31.6, 63.2, 94.7, and 138.9 MPa using a close-fit plunger die assembly (die length 135.3 mm and diameter of (6.30±0.5) mm). During pilot scale pelleting, customization of ground straw material was performed by adding steam exploded biomass in increments of 25% to non-treated ground straw for respective biomass at specific grind size. Ground straw samples were conditioned to 17.5% moisture content and 10% flaxseed oil was added to increase the bulk density and flowability of grinds, which resulted in the production of pellets. The quality of pellets from single pelleting experiments was ascertained by measuring their respective density and durability. In addition, the change in pellet density was measured after a storage period of one month to determine its dimensional stability. It was determined that applied pressure and pre-treatment were significant factors affecting the pellet density. Also, bigger grind sizes and lower applied pressures resulted in higher pellet relaxations (lower pellet densities) during storage of pellets. The pilot scale pellet mill produced pellets from ground non-treated straw at hammer mill screen sizes of 0.8 and 1.6 mm and customized samples having 25% steam exploded straw at 0.8 mm. It was observed that the pellet bulk density and particle density are positively correlated. The density and durability of agricultural straw pellets significantly increased with decrease in hammer mill screen size from 1.6 mm to 0.8 mm. Customization of agricultural straw by adding 25% of steam exploded straw by weight is possible, but it did not improve pellet quality. In addition, durability of pellets was negatively correlated to pellet mill throughput and was positively correlated to specific energy consumption. Keywords: biofuels, biomass, density, durability, pelleting, specific energy, steam explosion, pretreatment DOI: 10.3965/j.issn.1934-6344.2010.03.062-079 Citation: Phani Adapa, Lope Tabil, Greg Schoenau, Anthony Opoku. Pelleting characteristics of selected biomass with and without steam explosion pretreatment. Int J Agric & Biol Eng, 2010; 3(3): 62<span style="font-size: 9pt; line-height: 130%; font-family: